Peningkatan Pengetahuan Masyarakat Melalui Pendidikan Kesehatan Tentang Protokol Pencegahan Covid-19 Di Kelurahan Sungai Tiung Banjarbaruealth Education About the Covid-19 Prevention Health Protocol In Sungai Tiung Village, Banjarbaru City - Mariana, Evi Risa; Sajidah, Ainun; Fauziah, Erna (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Based on data from the Ministry of Health, which was published by BNPB Public Relations, Tuesday (26/1/2021), the cumulative total of Corona cases in Indonesia is 1,012,350. Looking at the 1 million figure, the Minister of Health stated that the public and government must work hard to overcome the pandemic. In order to stop the transmission of Covid 19, the Indonesian government will also vaccinate the Indonesian population. Even though the vaccine has been given, other efforts continue to be made by health experts and the public to end the increase in the Covid-19 virus. In several countries including Indonesia, the government has made health guidelines and protocols to deal with the Covid-19 virus. The results of research conducted by Fauziah, E. et al. In 2021, in Sungai Tiung Village, data was obtained that some people had a positive perception of administering the Covid-19 vaccine, but from the questionnaire questions, many respondents answered incorrectly on matters relating to health protocols for preventing Covid-19. Based on the results of this research and given the importance of health protocols for preventing Covid-19, it is necessary to increase knowledge through health education to the public about health protocols for preventing Covid-19.